The Role of Inadequate Self-Control Schema and Coping Styles in Addiction Potential Among Men - Jahangir, Fatemeh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the predictive role of inadequate self-control schema and coping styles in the addiction potential of men in Quds City.Methods and Materials: This research is applied in terms of purpose and descriptive-correlational in nature. All male individuals aged 20 to 40 residing in Quds County in 2024 constituted the statistical population of this study. A sample size of 254 individuals was selected through convenience sampling. The research tools included the Young Schema Questionnaire (short form, 1998), Lazarus and Folkman's Coping Styles Questionnaire (1985), and the Addiction Potential Scale by Videbucher (1992). Statistical analyses were performed using Pearson correlation coefficient and stepwise multiple regression tests in SPSS version 26.Findings: The results indicated that inadequate self-control schema and coping styles play a role in predicting men's addiction potential (P < 0.01). There was a significant correlation between inadequate self-control schema and men's addiction potential (P < 0.01). Additionally, the correlation between emotion-focused and problem-focused coping styles and men's addiction potential was significant (P < 0.01).Conclusion: In summary, this study demonstrates that inadequate self-control schemas and coping styles are significant predictors of addiction potential in men. The strong correlations found between these factors and addiction highlight the need for a deeper understanding of how maladaptive schemas and coping strategies contribute to addictive behaviors. These findings suggest that interventions focused on improving self-control and promoting effective coping mechanisms could be essential in mitigating addiction risks among men, paving the way for more targeted and effective prevention strategies.